THE PERCEPTION OF BODY IMAGE BY SCHOOL TEENAGERS (Fiep Bulletin - online, 2011)
Objectives: to verify the impact of voluntary and regular physical activity about the body image of teenagers. Methodology: descriptive study, with qualitative and quantitative approach and cross sectional. Sample of 524 school teenagers of both sexes aged between 12 and 20 years. The research received approve by Ethics Committee of the "Universidade Estadual de Montes Claros" Case No. 528/2006 of 12/15/2006. Was used the scales of valuation of silhouette Stunkard, Sorensen, Schulsinger (1983). Analytical and descriptive statistics (frequencies) through the correlation for nonparametric data. The coefficient of correlation used was Spearman. Results: practice of physical activity for male sex: initial phase (90.1%), medial (93.3%) and final (73.5%). For female: initial phase (83.2%), medial (64.9%) and final (92.9%). The general silhouette 3: male with 41.4% and female with 58.6%. The general silhouette 4: male with 52.6% and female with 47.6%. In silhouette of teenagers from male sex, for the practitioners or not of physical activity, the force of relation is moderate. The not practitioners have a perception of body image in a strong level of correlation. In female sex, the force of relation was moderate. When compared the superior silhouette with the inferior of practitioners of physical activity, the strength of relation continued moderate. Conclusions: the teenager men do practice more physical activity and tend to increase this practice between one phase and another in adolescence, while the teenagers tend to increase the level of physical inactivity. The teenager men presented significant correlations, having a good perception of the whole to their parts, and they choose the silhouette 3. The male sex practicing of physical activity of initial, medial and final phases has a better perception of its body image. The female sex from initial phase evidenced the sedentary one with a better perception of its body image and, in the medial and final phases, the practitioners have a better perception of their body image compared to the not practitioners.
Keywords: adolescents; body image; silhouettes